Turismo e beni culturali in Calabria: strategie di sviluppo basate sull’innovazione tecnologica - Skrame, Aurora; Furgiuele, franco; Muzzupappa, Maurizio (Università della Calabria, 2020)
My research was inspired by the analysis of the use of historical and cultural heritage in the Calabrian territory and by the evidence of the difficulties encountered in this. The use of historical and cultural heritage in Calabria is clearly less than in all other regions of Italy, despite the quantity and quality implicit in the offer. Most of the urban stratifications of the ancient nuclei are little known to classical tourism and to the population itself. In an area where only 20% of the surface is not historically populated, this is a situation that raises important questions and requires solutions. Tourism is a complex field, if the use does not reach the destination it is evident that one or more elements of the system do not work, do not collaborate or are not active. The identification and analysis of the gap between the strategies of the intervention plans and their application on the Calabrian territory was the starting point of this research. The aim of the research was therefore to deepen a complete methodology aimed at defining an effective and efficient "tourism product prototype", a project aimed at enhancing the Calabrian historical-archaeological heritage, focused on the most advanced virtual technology and integrated into the network. of existing services, to be amplified and improved, as a model to be reproduced in similar contexts, on the Calabrian territory. - To achieve this goal, I articulated and defined the research activity into three phases: The first analysis phase investigated three specific aspects: - In-depth study of the best examples and management strategies of tourism services and DMO (Destination Management Organization) operating in the field of historical-cultural heritage in Europe and in Italy, and identification of examples of good practices for an ideal DMO on the Calabrian territory according to the European reference quality parameters and indicators. - Study of regional and ministerial financing programs in the field of cultural tourism and infrastructure services in the Calabrian territory capable of supporting a specific project and the actors currently engaged in the territory. - Study of the best technological solutions in the context of the use of historical assets and the possible application on Calabrian archaeological areas and museums. The results I obtained from the first study phases described above have made it possible to identify the main critical issues of the infrastructural system, of the services in the field of cultural tourism and in particular have highlighted the absence in the application of innovative technologies that could expand in a way educational but also pleasant the offer linked to cultural heritage, involving new and more numerous users. Consequently I concentrated the second phase of the thesis work on the definition of an integrated and global intervention project (now become a Strategic Project financed by the Calabria Region and MIbac) which concerns the Ionian coast. It is obviously a highly symbolic territory (we are in Magna Grecia), one of the oldest and most precious testimonies of historical stratification in Italy, as well as the area with the highest concentration of sites that can be visited but little explored among the Italian ones (with a evident deficit in terms of attractiveness). The statistical-historical survey on the use of the area's sites (obtained from Istat and MIbac data) relegates it to the lowest places in the Italian ranking, with attendance that is limited to a few "lovers" or visits organized by schools. The seaside tourist potential of the Ionian belt is known but this is not absolutely integrated with the availability of areas and archaeological museums. My strategic proposal, third phase of the innovative activity of its kind, is divided into two phases: the coordination of the active rail transport service, with a new road passenger transport service (on call), which covers the entire Calabrian Ionian belt, from the station of Sibari to that of Bova, which involves the archaeological parks and museums of six distinct cultural tourist destinations; and the improvement of the cultural offer to visitors in each of the destinations, through didactic activities, projections and reconstructions usable in multiple ways based on virtual reality and the possibility to assist and participate in the excavation and recovery activities in the currently active archaeological sites, with itineraries customized for different categories of visitors. The media coverage promoted and curated by the Calabria Region, MIbac and FS, ensures a continuous tourist flow during the year. The final phase of the doctoral activity therefore concerns the definition of the integrated strategic model for the use of improvement technologies for one of the historical areas covered by the strategic project proposal. In detail, it is the design of a technologically advanced intervention of the route inside the archaeological site of Locri, in a more "user-oriented" rather than "expert-oriented" perspective. This approach aims to bring younger generations closer to the knowledge of historical and cultural heritage. To this end, I analyzed the results of the surveys planned and carried out with the various school groups in the last 3 years, with different universities, to identify the degree of interest and preferences towards multimedia technologies applied to historical heritage. Based on the results of the latter, I have developed a project of reconstruction and real navigation on the entire archaeological area of Locri Epizephiri, and in detail on its three most significant monumental buildings. The innovative approach of this research lies in having applied the in-depth knowledge of various fields of study such as architecture, history and engineering to find interdisciplinary solutions to the needs of critical issues emerging in the area of interest, of which;  humanistic / archaeological knowledge applied to the study of historical assets and finds,   the skills in the field of transport management applied to the organization of an integrated plan for the transport of people,   the notions of project management to connect and organize the services of the various stakeholders in the urban area, the timing and the economic framework,   the principles of civil and management engineering for the various processes related to the management of 3D technology and for reconstituted environments, with a view to global use,   knowledge of history and architecture for the harmonious elaboration of the elements and insertion in the current setting. could expand in a way educational but also pleasant the offer linked to cultural heritage, involving new and more numerous users. Consequently I concentrated the second phase of the thesis work on the definition of an integrated and global intervention project (now become a Strategic Project financed by the Calabria Region and MIbac) which concerns the Ionian coast. It is obviously a highly symbolic territory (we are in Magna Grecia), one of the oldest and most precious testimonies of historical stratification in Italy, as well as the area with the highest concentration of sites that can be visited but little explored among the Italian ones (with a evident deficit in terms of attractiveness). The statistical-historical survey on the use of the area's sites (obtained from Istat and MIbac data) relegates it to the lowest places in the Italian ranking, with attendance that is limited to a few "lovers" or visits organized by schools. The seaside tourist potential of the Ionian belt is known but this is not absolutely integrated with the availability of areas and archaeological museums. My strategic proposal, third phase of the innovative activity of its kind, is divided into two phases: the coordination of the active rail transport service, with a new road passenger transport service (on call), which covers the entire Calabrian Ionian belt, from the station of Sibari to that of Bova, which involves the archaeological parks and museums of six distinct cultural tourist destinations; and the improvement of the cultural offer to visitors in each of the destinations, through didactic activities, projections and reconstructions usable in multiple ways based on virtual reality and the possibility to assist and participate in the excavation and recovery activities in the currently active archaeological sites, with itineraries customized for different categories of visitors. The media coverage promoted and curated by the Calabria Region, MIbac and FS, ensures a continuous tourist flow during the year. The final phase of the doctoral activity therefore concerns the definition of the integrated strategic model for the use of improvement technologies for one of the historical areas covered by the strategic project proposal. In detail, it is the design of a technologically advanced intervention of the route inside the archaeological site of Locri, in a more "user-oriented" rather than "expert-oriented" perspective. This approach aims to bring younger generations closer to the knowledge of historical and cultural heritage. To this end, I analyzed the results of the surveys planned and carried out with the various school groups in the last 3 years, with different universities, to identify the degree of interest and preferences towards multimedia technologies applied to historical heritage. Based on the results of the latter, I have developed a project of reconstruction and real navigation on the entire archaeological area of Locri Epizephiri, and in detail on its three most significant monumental buildings. The innovative approach of this research lies in having applied the in-depth knowledge of various fields of study such as architecture, history and engineering to find interdisciplinary solutions to the needs of critical issues emerging in the area of interest, of which;  humanistic / archaeological knowledge applied to the study of historical assets and finds,   the skills in the field of transport management applied to the organization of an integrated plan for the transport of people,   the notions of project management to connect and organize the services of the various stakeholders in the urban area, the timing and the economic framework,   the principles of civil and management engineering for the various processes related to the management of 3D technology and for reconstituted environments, with a view to global use,   knowledge of history and architecture for the harmonious elaboration of the elements and insertion in the current setting.could expand in a way educational but also pleasant the offer linked to cultural heritage, involving new and more numerous users. Consequently I concentrated the second phase of the thesis work on the definition of an integrated and global intervention project (now become a Strategic Project financed by the Calabria Region and MIbac) which concerns the Ionian coast. It is obviously a highly symbolic territory (we are in Magna Grecia), one of the oldest and most precious testimonies of historical stratification in Italy, as well as the area with the highest concentration of sites that can be visited but little explored among the Italian ones (with a evident deficit in terms of attractiveness). The statistical-historical survey on the use of the area's sites (obtained from Istat and MIbac data) relegates it to the lowest places in the Italian ranking, with attendance that is limited to a few "lovers" or visits organized by schools. The seaside tourist potential of the Ionian belt is known but this is not absolutely integrated with the availability of areas and archaeological museums. My strategic proposal, third phase of the innovative activity of its kind, is divided into two phases: the coordination of the active rail transport service, with a new road passenger transport service (on call), which covers the entire Calabrian Ionian belt, from the station of Sibari to that of Bova, which involves the archaeological parks and museums of six distinct cultural tourist destinations; and the improvement of the cultural offer to visitors in each of the destinations, through didactic activities, projections and reconstructions usable in multiple ways based on virtual reality and the possibility to assist and participate in the excavation and recovery activities in the currently active archaeological sites, with itineraries customized for different categories of visitors. The media coverage promoted and curated by the Calabria Region, MIbac and FS, ensures a continuous tourist flow during the year. The final phase of the doctoral activity therefore concerns the definition of the integrated strategic model for the use of improvement technologies for one of the historical areas covered by the strategic project proposal. In detail, it is the design of a technologically advanced intervention of the route inside the archaeological site of Locri, in a more "user-oriented" rather than "expert-oriented" perspective. This approach aims to bring younger generations closer to the knowledge of historical and cultural heritage. To this end, I analyzed the results of the surveys planned and carried out with the various school groups in the last 3 years, with different universities, to identify the degree of interest and preferences towards multimedia technologies applied to historical heritage. Based on the results of the latter, I have developed a project of reconstruction and real navigation on the entire archaeological area of Locri Epizephiri, and in detail on its three most significant monumental buildings. The innovative approach of this research lies in having applied the in-depth knowledge of various fields of study such as architecture, history and engineering to find interdisciplinary solutions to the needs of critical issues emerging in the area of interest, of which;  humanistic / archaeological knowledge applied to the study of historical assets and finds,   the skills in the field of transport management applied to the organization of an integrated plan for the transport of people,   the notions of project management to connect and organize the services of the various stakeholders in the urban area, the timing and the economic framework,   the principles of civil and management engineering for the various processes related to the management of 3D technology and for reconstituted environments, with a view to global use,   knowledge of history and architecture for the harmonious elaboration of the elements and insertion in the current setting.
Università della Calabria. Dipartimento di Ingegneria Meccanica, Energetica e Gestionale. Dottorato di Ricerca in Ingegneria Civile ed Industriale DICI – Ciclo XXXII
Keywords: Turismo; Beni culturali; Tecnologia; Trasporto ferroviario